Factors affecting online coffee purchases in the Covid-19 pandemic era: consumer case study at Jotey Coffee Shop (Research, Society and Development, 2021)
Research in journal aim for analyze the factors that influence the purchase of coffee online in the era of the Covid 19 pandemic at the Jotey Coffee Shop. This research uses methodde quantitative. The population in this study are online buyers, especially Jotey coffee at the Jotey Coffee Shop, East Bekasi with a sample size of240 consumers Kedai Jotey, where the sample uses the Hair method. Test the hypothesis proposed in this study done with tool test analysis regression and hypothesis partial and simultaneous by using software Smartpls 3.2.9. Results analysis show that: 1) Communication a positive and significant effect on online coffee purchasing decisions, 2) Process has a positive and significant effect on online coffee purchasing decisions, 3) Price has a negative and significant effect on online coffee purchasing decisions, 4) Product has a positive and significant effect on online purchasing decisions contemporary coffee, 5) Character has a positive and significant effect on online purchasing decisions for contemporary coffee, and 6) Risk does not have a positive and significant effect on online purchasing decisions for contemporary coffee at the Jotey Coffee Shop.